g(-5) = ? Since they give you the value of x, which is -5, you can substitute/plug it into the equation.
g(x) = -3x - 21
g(-5) = -3(-5) - 21 [two negative signs cancel each other out and become positive]
g(-5) = 15 - 21
g(-5) = -6
g(6) = ? The value of x is 6
g(x) = -3x - 21 Substitute 6 into x
g(6) = -3(6) - 21
g(6) = -18 - 21
g(6) = -39
g(3.5) = ? The value of x is 3.5
g(x) = -3x - 21 Substitute 3.5 into x
g(3.5) = -3(3.5) - 21
g(3.5) = -10.5 - 21
g(3.5) = -31.5
g(-12) = ? The value of x is -12
g(x) = -3x - 21 Substitute -12 into x
g(-12) = -3(-12) - 21
g(-12) = 36 - 21
g(-12) = 15